Factors associated with eating behaviors in older adults from a socioecological model perspective - Wang, Xue; Wu, Yibo; Miao, Juanxia; Pu, Keping; Ming, Wai-Kit; Zang, Shuang (BMC public health, 2023)
Background The eating behaviors of older adults are associated with multiple factors. To promote older adults' healthy diets, it is imperative to comprehensively study the factors associated with the eating behaviors of the aging population group. This study aimed to probe the associated factors of older adults' eating behaviors from a socioecological model (SEM) perspective. Methods In 2021, a cross-sectional survey was performed to recruit participants in China. The survey data were analyzed using a multivariate generalized linear model to identify the factors associated with eating behaviors in older adults. Standardized regression coefficients ([beta]) and 95% confidence intervals (CIs) were estimated using a multivariate generalized linear model. Results The survey contained 1147 valid older adult participants. Multivariate generalized linear model results showed that older adults with older age [aged 71-80 ([beta] = -0.61), [greater than or equal to] 81 ([beta] = -1.12)], conscientiousness personality trait ([beta] = -0.27), and higher family health levels ([beta] = -0.23) were inclined to have better eating behaviors. The older adults with higher education levels [junior high school and high school ([beta] = 1.03), junior college and above ([beta] = 1.71)], higher general self-efficacy ([beta] = 0.09), more severe depression symptoms ([beta] = 0.24), and employment ([beta] = 0.82) tended to have poorer eating behaviors. Conclusions This study identified factors that are specifically associated with older adults' eating behaviors from an SEM perspective. The comprehensive multiple-angle perspective consideration may be a valuable idea for studying healthy eating behaviors in older adults. Keywords: Eating behavior, Older adults, Socioecological model, China